MITOLOGI JAWA DALAM CERITA CALON ARANG KARYA PRAMOEDYA ANANTA TOER - Hastuti, Hastuti (LPPM STKIP PGRI Bandar Lampung, 2020)
This study aims to describe Javanese mythology in Pramoedya Ananta Toer's story of Calon Arang. The method that will be used by researchers in this research is descriptive method. From the research results in the novel Cerita Calon Arang by Pramoedya Ananta Toer, there are three mythologies. First, belief in mantras, the second is offering rituals, and the third is ritual worship.